2017
DOI: 10.4103/ijo.ijo_874_16
|View full text |Cite
|
Sign up to set email alerts
|

Descemet stripping automated endothelial keratoplasty

Abstract: Endothelial keratoplasty is at present the gold standard for surgical treatment of corneal endothelial pathologies not associated with significant corneal scar. Tremendous progress has been made in recent years in improving the technology of endothelial keratoplasty techniques, such as descemet stripping automated endothelial keratoplasty (DSAEK) and descemet membrane endothelial keratoplasty. In this review, we discuss the current techniques and outcomes of DSAEK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 98 publications
1
20
0
Order By: Relevance
“…Results of this study showed acceptable BSCVA in the average duration of one year post DSAEK. BSCVA was almost in the same range as that in prior studies (2,3). New methods of DSAEK including ultrathin and double pass microkeratome technique achieve better BSCVA outcomes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Results of this study showed acceptable BSCVA in the average duration of one year post DSAEK. BSCVA was almost in the same range as that in prior studies (2,3). New methods of DSAEK including ultrathin and double pass microkeratome technique achieve better BSCVA outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…Preparation of donor tissue in DSAEK is assisted by an automated microkeratome, which dissects a disc containing the endothelium, Descemet's membrane and a thin layer of posterior stroma (2). A posterior lamellar corneal lenticule is cut from the donor cornea by a microkeratome, which can be set to harvest a desired thickness.…”
Section: Introductionmentioning
confidence: 99%
“…4). 122 One of the advantages of these EK techniques is that the graft can be fixed without sutures using an air bubble. Once the air resorbs, the graft is unsupported and can detach from the posterior cornea.…”
Section: Resultsmentioning
confidence: 99%
“…DSAEK has become the gold standard of EK in recent years due its efficacy, safety, and reproducibilty in achieving optimal visual outcomes. [ 62 63 ] The procedure is fairly reliable with a low rate of complications. Over the past few years, there has been a constant attempt to reduce the graft thickness (GT) without increasing the risk of tissue loss while donor preparation since a thinner graft is associated with a better visual outcome.…”
Section: Classificationmentioning
confidence: 99%
“…In the standard single-pass technique that uses microkeratome head of size 350 μm, the average thickness of harvested endothelial grafts may be 150–250 μm. [ 62 ] In recent times, following two techniques that can harvest thinner donor lenticules are being successfully used:…”
Section: Classificationmentioning
confidence: 99%